Drug–food and drug–alcohol interactions: Pharmacists’ knowledge gaps and patient safety concerns in the United Arab Emirates - Taima Qudah; Leen Fino; Razan I. Nassar; Suhad Abumueis (PLoS ONE, 2026)
Pharmacists play a critical role in promoting medication safety through patient counselling and identification of potential interactions. However, knowledge regarding drug–food interactions (DFIs) and drug–alcohol interactions (DAIs) among community pharmacists in the United Arab Emirates (UAE) has not been previously examined. This cross-sectional study assessed pharmacists’ knowledge of DFIs, DAIs, and drug–food administration timing, and identified factors associated with higher knowledge levels using a validated self-administered 24-items questionnaires. The survey assessed sociodemographic and professional characteristics, knowledge of DFIs, DAIs, and drug-food timing. Descriptive statistics and multiple linear regression analyses were performed using SPSS v28.0 to determine predictors of total knowledge scores. Pharmacists demonstrated moderate knowledge, with mean scores of 8.62/12 for DFIs, 5.84/12 for drug–food timing, and 4.70/6 for DAIs (total score 19.16/30). High awareness was observed for interactions such as caffeine–diazepam (76.3%) and methotrexate–alcohol (81.0%), whereas only 25.9% identified potassium-rich foods’ interaction with spironolactone. Higher knowledge scores were associated with being male (p < 0.001), aged 20–29 years (p = 0.041), having ≥6 years of experience (p = 0.004), and higher self-perceived knowledge (p < 0.001). These findings highlight important knowledge gaps that may affect patient safety. Targeted continuing education and integration of DFI/DAI content into pharmacy curricula are recommended to strengthen counselling practices and improve medication safety outcomes.